Impact of COVID-19 Pandemic on Dermatologists and Dermatology Practice - Bhat, Yasmeen Jabeen (Indian Dermatol Online J, 2020)
The COVID-19 pandemic has directly or indirectly affected every human being on this planet. It's impact on the healthcare system has been devastating. The medical fraternity across the world, including India, is facing unprecedented challenges in striving to cope up with this catastrophic outbreak. Like all other specialties, dermatology practice has been profoundly affected by this pandemic. Measures have been taken by dermatologists to control the transmission of the virus, whereas providing health care to patients in the constrained environment. Preventive measures such as social distancing and hand hygienic practices along with patient education is being prioritized. Dermatological conferences and events scheduled across the globe in the first half of year 2020 have been either cancelled or postponed to discourage gatherings. Rationalization of resources and practice of teledermatology are being encouraged in current scenario. Non-urgent visits of the patients are being discouraged and elective dermatology procedures are being postponed. Many national and international dermatology societies have recently proposed recommendations and advisories on usage of biologicals and immunomodulators in present context of COVID-19 pandemic. Urticarial, erythematous, varicelliform, purpuric and livedoid rash as well as aggravation of preexisting dermatological diseases like rosacea, eczema, atopic dermatitis, and neurodermatitis rash have been reported in Covid-19 patients. Self medications and poor compliance of dermatology patients in addition to lack of proper treatment protocols and monitoring are a serious concern in the present scenario. Strategies for future course of action, including the dermatology specific guidelines need to be framed. This issue includes a special symposium on dermatology and COVID-19 having recommendations from special interest groups (SIGs) of Indian Association of Dermatologists, Venereologists and Leprologists (IADVL) Academy on leprosy, dermatosurgery, lasers and dermoscopy.